Effects of humidity on dust particle removal during solar panel cleaning. (14th January 2022) - Chen, E.Y; Renner, P; Lee, K; Guo, B; Liang, H
Abstract: Solar panel cleaning is important to maintain the efficiency of energy production. In this research, we investigated the effects of relative humidity and condensation on the effectiveness of cleaning. The dust particles are subjected to various forces once they are deposited on the surface of a solar panel. When the dust particles continue to build up, they are also subjected to the adhesion forces from the neighboring dust particles. The adhesion forces from the substrates and the neighboring particles are dependent on the ambient conditions. Fundamentally, the interaction between the adhesion force of particle-particle and particle-substrate under various conditions was discussed in this manuscript.